Effectiveness of Post-Abortion Family Planning Counseling Program on Nurses and Midwives’ Practices in Middle Euphrates Maternity Hospitals - Seger, Hadeel; abbas, iqbal (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: To determine the effectiveness of post-abortion family planning counseling program on nurses and midwives’ practices and to predict the variables which may effect on their practices Methodology: A quasi experimental study was conducted from 23th April 2017 to 14th March 2018 in three governorates in Middle Euphrates of Iraq: (Holy Karbala, Al - Najef Al Ashraf and Babylon) on nurses and midwives who work at maternity hospitals. Systematic random sampling was used to select 122 nurses and midwives, (60) of them for study group and (62) for control group. A checklist is an instrument that evaluate the practices which included 50 items. Validity of content was determined through reviewing it by (16) experts and reliability of tool was determined through a pilot study. descriptive and inferential statistics were used to analyze the data. Results: The results of study revealed that there were high statistical differences in nurses and midwives’ practices between study and control groups at posttest, while there were no differences between both groups at pretest. Variables: (age, educational level, social status and years of experiences) were not effect on their practices. Recommendations: Establishing teaching and training courses concerning post abortion family planning counseling for all nurses and midwives who work at maternity hospitals in middle Euphrates